Analisis Peluang Kejadian Deret Hari Kering Selama Musim Tanam Di Kota Ambon - Laimeheriwa, Semuel (Pattimura University, Ambon, 2014)
Drought is one of natural disaster that is commonly difficult to avoid and become a serious problem in crop production in Indonesia. Therefore, this study was conducted to determine the probability of dry spell during several days and its used to determine safety growing season in Ambon City. Data analyse was conducted in three steps, that is (1) determination of growing season by FAO (1978); ( 2) analysis of dry spell probability; and (3) determination safety growing season. Result of analysis indicated that the growing season in Ambon City took place during 10 months from December to September next year. During the growing season, the probability occuring of long dry spell (as much as 10, 15, and 20 days) was relatively smaller, less than 45%. The Probability of the dry spell as much as 10 days was equal to 13% on Juli and up to 42% on September; more than as much as 15 days was equal to 3% on April and May; and up to 19% on September, and as much as 20 days was equal to 0% on April and May; and up to 13% on September. High dry spell probability was generally occurred by the end of the growing season in September, whereas the lowest probability of dry spell occured in April and May when almost has no long dry spell.